Astrocytes in the nucleus of the solitary tract are activated by low glucose or glucoprivation: evidence for glial involvement in glucose homeostasis - McDougal, David H.; Hermann, Gerlinda E.; Rogers, Richard C. (Frontiers in Neuroscience, 2013)
Glucose homeostasis is maintained through interplay between central and peripheral control mechanisms which are aimed at storing excess glucose following meals and mobilizing these same stores during periods of fasting. The nucleus of the solitary tract (NST) in the dorsal medulla has long been associated with the central detection of glucose availability and the control of glucose homeostasis. Recent evidence has emerged which supports the involvement of astrocytes in glucose homeostasis. The aim of the present study was to investigate whether NST-astrocytes respond to physiologically relevant decreases in glucose availability, in vitro, as well as to the presence of the glucoprivic compound 2-deoxy-D-Glucose. This report demonstrates that some NST-astrocytes are capable of responding to low glucose or glucoprivation by increasing cytoplasmic calcium; a change that reverses with restoration of normal glucose availability. While some NST-neurons also demonstrate an increase in calcium signaling during low glucose availability, this effect is smaller and somewhat delayed compared to those observed in adjacent astrocytes. TTX did not abolish these hypoglycemia mediated responses of astrocytes, suggesting that NST-astrocytes may be directly sensing low glucose levels as opposed to responding to neuronal detection of hypoglycemia. Thus, chemodetection of low glucose by NST-astrocytes may play an important role in the autonomic regulation of glucose homeostasis.